2019
DOI: 10.1101/664599
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Associations between meteorological variables, vector indices and dengue hospitalizations in Can Tho, Vietnam: a field survey

Abstract: 18 19 42The house-(HI), container-(CI), Breteau (BI), and pupal (PI) indices were associated with relative 43 humidity (1-month lag, IRR HI =1.10 (95% CI 1.06, 1.13) per 1% increase), IRR CI =1.10 (95% CI 1.02, 44 1.19), IRR BI =1.17 (95% CI 1.14, 1.21), IRR PI =1.12 (95% CI 1.10, 1.14)). Vector indices were also 45 associated with precipitation (1-month lag) and to a lesser degree, hours of sun and mean 46 temperature. Ae. aegypti larval density was associated with not cleaning water storage containers 47 (RR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…This is because at low temperatures they prevent the development of the Aedes aegypti mosquito [43]. In Can Tho (Mekong, Vietnam), [56] founded that the relative humidity was the most important meteorological predictor for dengue hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…This is because at low temperatures they prevent the development of the Aedes aegypti mosquito [43]. In Can Tho (Mekong, Vietnam), [56] founded that the relative humidity was the most important meteorological predictor for dengue hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in Vietnam have reported the effect of increased temperatures on the risk of hospital admission in general populations, 35,36 in specific age groups, 37 and in specific diseases. [38][39][40] However, to the best of the author's knowledge, there is no evidence of the heat effect on hospital admission risk among farmers in Vietnam. Therefore, this study aims to assess the effect of high temperatures on hospitalization risk for all causes and heat-sensitive diseases among Vietnamese farmers.…”
mentioning
confidence: 99%